Parametric Analysis of a Steel Industrial Building Frame Considering Wind Load, Dampers and Bracings Using ETABS - Swapnil Jain; Murlidhar Chourasiya; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2022)
In addition to gravity stresses, the building’s structural structure must handle lateral loads caused by earthquakes and wind. A lateral load causes significant stresses and instability, which results in vibration and drift. If industrial steel structures are not designed to withstand lateral loads, they may collapse, resulting in the death or destruction of people or property. As a result, the structure must not only be strong enough to withstand gravity loads, but also stiff enough to withstand lateral forces. According to a review of the literature, LLRSS (Lateral load Resisting structural system) components such as base isolation and dampers are used to manage seismic vibration and lateral drift. This research compares the performance of a G+4 steel frame building with and without a damper. It is a rectangular structure with an industrial operation. The planned building’s structural frame is a unique steel moment resisting frame (SMRF). ETABS is used to perform structural analysis and design. The structure’s dynamic behaviour under wind and seismic loads is investigated using response spectrum analysis. Wind and earthquake vibrations are reduced by the usage of dampers. Engineers can improve the building’s resilience by employing dampers. Fluid viscous dampers are investigated in depth in this research. The parametric investigation of Dynamic analysis of 3D industrial steel structure braced with varied bracing configurations and dampers with different mass ratios utilising software (ETABS). For the structural stability of the building structure under seismic loads, X-bracing bracing configurations were adopted. A comparison with a general steel construction was done, and the bracing structure and dampers were examined.